2015
DOI: 10.1074/jbc.m115.636407
|View full text |Cite
|
Sign up to set email alerts
|

Microprocessor Complex Subunit DiGeorge Syndrome Critical Region Gene 8 (Dgcr8) Is Required for Schwann Cell Myelination and Myelin Maintenance

Abstract: Background: Dgcr8 regulates primary miRNA processing in the nucleus. Results: Conditionally ablating Dgcr8 in Schwann cells during development or in adulthood causes defects in myelin formation and gene expression characteristic of immature and denervated (injured) Schwann cells. Conclusion: Dgcr8 is needed for myelin formation and maintenance. Significance: miRNAs synchronize the translation of genes essential to myelin formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 92 publications
3
38
0
Order By: Relevance
“…The analysis identified 4091 genes of peripheral nerves that were occupied by H3K27me3 around the transcription start site (± 7 kb), including 532 genes that are normally induced (> 2 fold) after injury, and revealed the H3K27me3 enrichment at silent or low-expressed genes (RPKM= < 1) (Figure 4A and Supporting Information Table 1). For example, H3K27me3 was highly enriched at a silenced gene of peripheral nerves, sonic hedgehog ( Shh ) (Arthur-Farraj et al 2012; Lin et al 2015), and over 73% of H3K27me3-occupied genes were expressed at very low levels (RPKM < 5). Interestingly, H3K27me3 was also abundant at some highly expressed genes, such as desert hedgehog (Dhh), a signaling molecule required for the structural and functional integrity of the peripheral nerves (Parmantier et al 1999; Sharghi-Namini et al 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis identified 4091 genes of peripheral nerves that were occupied by H3K27me3 around the transcription start site (± 7 kb), including 532 genes that are normally induced (> 2 fold) after injury, and revealed the H3K27me3 enrichment at silent or low-expressed genes (RPKM= < 1) (Figure 4A and Supporting Information Table 1). For example, H3K27me3 was highly enriched at a silenced gene of peripheral nerves, sonic hedgehog ( Shh ) (Arthur-Farraj et al 2012; Lin et al 2015), and over 73% of H3K27me3-occupied genes were expressed at very low levels (RPKM < 5). Interestingly, H3K27me3 was also abundant at some highly expressed genes, such as desert hedgehog (Dhh), a signaling molecule required for the structural and functional integrity of the peripheral nerves (Parmantier et al 1999; Sharghi-Namini et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Many injury-induced genes encode intercellular signaling molecules such as sonic hedgehog ( Shh ), which is silenced throughout Schwann cell development prior to injury (Lin et al 2015). Schwann cells in injured nerve induce genes encoding factors that promote axon survival and regeneration: e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Shh gene, which is not normally expressed in SCs, is activated upon nerve injury. Lin et al suggested that Sox-2 and Shh were involved in adhesion in SCs [36]. The mRNA expression patterns of Dgcr8, Zeb2, Dixdc1, Sox2, Shh, Gpr126, and Birc2 detected by qRT-PCR were opposite to the MeDIP analysis data with significance ( p < 0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Glenn and Talbot [35] found that Gpr126 was essential for SCs to initiate myelination and addressed the role of Gpr126 signaling in myelin maturation and maintenance. Dgcr8 is responsible for modulation of myelin formation and maintenance as well as suppression of an injury-related gene expression program in SCs [36]. Quintes et al [37] proved that Zeb2 is essential for Schwann cell differentiation, myelination, and nerve repair.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently found that let‐7 miRNAs drive the onset of myelination (Gökbuget et al, ), and loss of Dgcr8 or Dicer in SCs impaired this developmental process (Bremer et al, ; Lin, Oksuz, Hurley, Wrabetz, & Awatramani, ; Pereira et al, ; Verrier, Semple‐Rowland, Madorsky, Papin, & Notterpek, ; Yun et al, ). Dgcr8‐ablated SCs appeared to be more affected than Dicer‐ablated SCs, in line with potential additional functions of the microprocessor in myelination (Lin et al, ). Furthermore, aberrant expression of repair SC markers and failure of proper myelin maintenance were noted.…”
Section: Introductionmentioning
confidence: 99%